New Therapeutics to Treat Castrate-Resistant Prostate Cancer - Ömer Acar; Tarık Esen; Nathan A. Lack (The Scientific World Journal)
The effective treatment of castrate-resistant prostate cancer (CRPC) has proven to be very challenging. Until recently, docetaxel was the only therapeutic demonstrated to extend overall patient survival. Yet recently, a considerable number of new therapeutics have been approved to treat CRPC patients. These remarkable advances now give new tools for the therapeutic management of late-stage prostate cancer. In this review, we will examine mechanistic and clinical data of several newly approved therapeutics including the chemotherapeutic cabazitaxel, antiandrogen enzalutamide, endocrine disruptor abiraterone acetate, immunotherapy sipuleucel-T, and bone-targeting radiopharmaceutical alpharadin. In addition, we will examine other promising therapeutics that are currently in Phase III trials.